The Influence of Online Advertising on Smartphone Purchase Intentions During Covid-19 Pandemic - Br Sembiring, Agika Wasinta; Fahlevi, Renza (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2023)
Purpose– The study aims to determine the effect of online advertising on the intention to buy a smartphone during the Covid-19 pandemic in Batam. Methodology/approach– Research using a comparative causal method. The population in this study is the Batam people. The research sample is the people of Batam who have seen the smartphone online advertisements and have the intention to buy a smartphone. The samples collected in the study were 310 respondents. The data is processed using SmartPLS and SPSS software. Findings– The results showed Informativeness, Entertainment, Incentives, and Credibility had significant positive effect towards Advertising Value. Advertising Value had a significant positive effect on purchase intention. It was also found that Irritation had no significant effect on Advertising Value.Novelty/value– This study highlight the importance of Informativeness, Entertainment, Incentives, and Credibility to Advertising Value for designing appropriate advertisements in the future in order to increase purchase intention. Keywords: Informativeness, Irritation, Entertainment, Incentives, Credibility, Advertising Value, Purchase Intention, Smartphone